2014
DOI: 10.1016/j.jvs.2013.10.104
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of aneurysm diameter and body size for predicting abdominal aortic aneurysm rupture in men and women

Abstract: Objectives Women have been shown to have up to a four-fold higher risk of abdominal aortic aneurysm (AAA) rupture at any given aneurysm diameter compared to men, leading to recommendations to offer repair to women at lower diameter thresholds. Although this higher risk of rupture may simply reflect greater relative aortic dilatation in women who have smaller aortas to begin with, this has never been quantified. Our objective was therefore to quantify the relationship between rupture and aneurysm diameter relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
134
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(149 citation statements)
references
References 40 publications
10
134
2
3
Order By: Relevance
“…Of 100 potentially relevant articles screened initially, nine eligible studies 8,[11][12][13][14][15][16][17][18] were identified. Furthermore, two relevant studies 6,7 were added through a manual search.…”
Section: Resultsmentioning
confidence: 99%
“…Of 100 potentially relevant articles screened initially, nine eligible studies 8,[11][12][13][14][15][16][17][18] were identified. Furthermore, two relevant studies 6,7 were added through a manual search.…”
Section: Resultsmentioning
confidence: 99%
“…It has been debated, however, whether BMI is associated with AAA rupture. Although the RESCAN meta-analysis [5] of fi ve studies (including only 80 AAA ruptures) demonstrated a negative association between BMI and AAA rupture, a number of studies [39][40][41] suggest no association. Further investigations are required to elucidate why BMI is not associated with AAA growth despite its trend toward a positive association with AAA presence and to determine whether BMI is associated with AAA rupture.…”
Section: Discussionmentioning
confidence: 98%
“…Abdominal aortic aneurysm rupture (AAAR) is one of the major issues in both vascular surgery and vascular disease-related mortality [1,2]. The primary reason for the continued high mortality in AAAR patients is that many of these patients are unaware of the presence of this illness.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an abdominal aortic aneurysm (AAA) is often asymptomatic, and its rupture, which is often experienced as abdominal pain or a backache, can be misdiagnosed by both the patient and medical staff, particularly if no previous knowledge of the disease has been reported [2]. According to clinical observations, the risk of an AAAR significantly increases with an increase in the aneurysm's diameter [1]. Among the other factors that potentially can be related to the rupture of an aortic aneurysm, uncontrolled arterial hypertension, smoking and increased age should be considered [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation